Metal-Free Catalytic Aromatic C–H Borylation - Zhang, Hua; Wang, Li (Synlett, 2020)
In recent decades, C–H borylation has undergone rapid development and has become one of the most important and efficient methods for the synthesis of organoboron compounds. Although transition-metal catalysis dominates C–H borylation, the metal-free approach has emerged as a promising alternative strategy. This article briefly summarizes the history of metal-free aromatic C–H borylation, including early reports on electrophilic C–H borylation and recent progress in metal-free catalytic intermolecular C–H borylation; it also highlights our recent work on BF3·Et2O-catalyzed C2–H borylation of hetarenes. Despite these recent advances, comprehensive mechanistic studies on various metal-free catalytic aromatic C–H borylations and novel processes with a wider substrate scope are eagerly expected in the near future.
Keywords: C–H activation; borylation; metal-free reaction; catalysis; organoboron compounds